IFNα subtype-specific susceptibility of HBV in the course of chronic infection - Xie, Xiaohong; Karakoese, Zehra; Ablikim, Dilhumare; Ickler, Julia; Schuhenn, Jonas; Zeng, Xiaoqing; Feng, Xuemei; Yang, Xuecheng; Dittmer, Ulf; Yang, Dongliang; Sutter, Kathrin; Liu, Jia (Frontiers in Immunology, 2022)
Chronic hepatitis B virus (HBV) infection continues to be a major health problem worldwide and remains hard to be cured. Therapy with interferon (IFN) α is an important method for the clinical treatment of chronic hepatitis B. IFNα exhibits direct antiviral effects as well as immunomodulatory activities, which can induce sustained antiviral responses in part of the treated chronic hepatitis B patients. Numerous IFNα subtypes with high sequence identity between 76-96% exist which are characterized by diverse, non-redundant biological activities. Our previous studies have demonstrated that the clinically approved IFNα2 is not the most effective subtype for the anti-HBV treatment among all IFNα subtypes. So far very little is known about the IFNα subtype expression pattern during early HBV infection and the IFNα subtype-specific susceptibility during persistent HBV infection as well as its related cellular mechanism. Here we determined the Ifna subtype mRNA expression during acute and chronic HBV infection by using the well-established hydrodynamic injection (HDI) mouse model and we revealed a transient but strong expression of a panel of Ifna subtypes in the spleen of HBV persistent replication mice compared to HDI controls. Immunotherapy with distinct IFNα subtypes controlled chronic HBV infection. IFNα subtype-mediated antiviral response and immune activation were comprehensively analyzed in an AAV-HBV persistent infection murine model and murine IFNα2 was identified as the most effective subtype in suppression of HBV replication. Further analysis of the immune response revealed a strong immunomodulatory activity of murine IFNα2 on splenic and intrahepatic NK and T cell activation during persistent HBV infection. Taken together, our data provide IFNα subtype-specific differences in the antiviral and immunomodulatory effector responses and a strong expression of all IFNα subtypes in the spleen during persistent HBV infection in mice. This knowledge will support the development of novel immunotherapeutic strategies for chronic hepatitis B infection.